Dietary inulin ameliorates obesity-induced severe acute pancreatitis via gut-pancreas axis - Xin Li; Pan Zheng; Yaoyu Zou; Langyi Guan; Nianshuang Li; Jianping Liu; Nonghua Lu; Yin Zhu; Cong He (Gut Microbes)
Obesity is a definitive factor of severity and mortality of acute pancreatitis (AP), and gut microbiota dysbiosis is involved in its pathogenesis. However, the effect of gut microbiota modulation by dietary components on high fat diet (HFD)-induced severe AP remains unclear. Here, we found that the inulin, a soluble dietary fiber, mitigated pancreatic injury and systematic inflammation in mice fed HFD, which was dependent on gut microbiota as this protective effect was attenuated in germ-free mice. Inulin treatment suppressed the overgrowth of pathogenic bacteria Escherichia Shigella, Enterococcus, Klebsiella, while increased the abundance of probiotics Akkermansia. Fecal microbiota transplantation from inulin-treated mice to recipient mice reduced pancreatic damage and remodeled intestinal homeostasis. Additionally, inulin increased fecal short chain fatty acids (SCFAs), strengthened gut barrier and restored Paneth cells. The beneficial effect of inulin on improving pancreatic damage and leaky gut was diminished after the suppression of SCFAs. Notably, SCFAs administration, especially butyrate, to HFD mice blocked pancreatic and intestinal injury with the inhibition of histone deacetylase 3 (HDAC3), and pharmacological HDAC3 inhibition mimicked the ameliorative effect of SCFAs. Mechanically, butyrate modulated macrophage M1/M2 polarization balance by suppressing HDAC3 and subsequent acetylation of histone H3K27. Collectively, our data offer new insights into the gut microbiota-pancreas axis that may be leveraged to augment the potential supplementation of prebiotic inulin in the management of obesity associated severe AP.